MOTIVASI PBB MEMBENTUK UNITED NATION MISSION IN DARFUR (UNAMID) SEBAGAI PEACEKEEPING OPERATION PBB PADA KONFLIK SUDAN 2007 - Deldiya "; Yuli Fachri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research aims to analyze how UNAMID peacekeepers have resolved armed conflict in the Darfru region of Sudan since 2003. The Darfur conflict involves the Sudanese government assisted by the Janjaweed militia with Sudan Liberation Movement (SLM) and Justice Equality Movement (JEM) groups. The Darfur conflict is of international concern due to attacks by Janjaweed militias against Darfur civilians. Resulted the UN and the African Union decided to intervene in resolving the conflict that occurred in Darfur, Sudan.The data used in this study a secondary data. Secondary data was obtained through library research, and search online media research. The writer uses of the pluralism perspective and organization level of analysis. Theories used in this study is based on the organization theory by Clive Archer.The research result is indicate that in resolving the Darfur conflict, UN forming a peace operation to wit UNMIS and UNAMID. The African Union participated in resolving the Darfur conflict also forming a peace operation that is AMIS. As a result of the inadequate role of AMIS and UNMIS due to difficulties with logistics, funding and lack of experience in the field of peacekeeping operations, the AMIS mandate was replaced by UNAMID. UNAMID's various program efforts in Darfur to protect civilians from attacks by Janjaweed militia. Although UNAMID often encounters obstacles that hinder the realization of a peace mission in Darfur.Keywords: AMIS, UNMIS, UNAMID, Peacekeeping Operation, UNSC, African Union, Janjaweed Militia, SLM, JEM, Sudan Government.